Artificial Spider Silk Based Programmable Woven Textile for Efficient Wound Management. (24th October 2021) - Cheng, Cheng; Qiu, Yumeng; Tang, Shimeng; Lin, Baoyang; Guo, Maoze; Gao, Bingbing; He, Bingfang
Abstract: Trauma often causes great damage to the human body's skin and soft tissues, and results in severe fractures. Though the regeneration of wound tissue and the sensing of wound secretions have been studied extensively, wound therapy remains challenging. Herein, an intelligent artificial spider silk protein (spidroin) composite programmable woven textile (i‐SPT) with high tensile properties is developed, which possesses biochemical sensing abilities and air permeability as well as motion monitoring capabilities for wound management. The patterned microfluidic channels on i‐SPT allow liquids to flow spontaneously through the channels, and the pH‐responsive photonic crystals (PC) enables the i‐SPT for sensitive hydrogen ion concentration sensing in wound area, meanwhile, the highly integrated microelectronic circuit on i‐SPT endowed high sensitivity for motion monitoring. The capability of i‐SPT in promoting wound healing has been illustrated by the treatment of the full skin wounds of diabetic mouse models. Thus, i‐SPT provides a novel and effective solution for wound management. Abstract : Intelligent artificial spider silk protein (spidroin) composite programmable woven textile (i‐SPT) with high tensile properties is developed, which possesses biochemical sensing abilities and air permeability as well as motion monitoring capabilities for wound management.